1985
DOI: 10.1161/01.cir.71.6.1129
|View full text |Cite
|
Sign up to set email alerts
|

Platelet activation and secretion associated with emotional stress.

Abstract: Platelets are believed to play a role in the pathogenesis of atherosclerosis and of the vascular obstruction that causes the acute complications of coronary artery disease. Since specific behavioral patterns appear to be related to the development of coronary artery disease and since emotional stress may predispose an individual to acute cardiovascular ischemia, it was hypothesized that platelet activation by catecholamines might be involved in these events. To study emotional stress, plasma samples were obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
77
1
2

Year Published

1989
1989
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(86 citation statements)
references
References 35 publications
6
77
1
2
Order By: Relevance
“…232,233 Recently, the effects of acute psychological stress on indices of coagulation have been studied during laboratory mental stress tasks 234,235 and during various naturalistic stressors. 236,237 In both situations, significant, but not always consistent, platelet abnormalities have been observed. Acute laboratory mental stress also causes hemoconcentration through stress-induced decreases in plasma volume, as observed in various studies.…”
Section: Coagulation Effectsmentioning
confidence: 91%
See 1 more Smart Citation
“…232,233 Recently, the effects of acute psychological stress on indices of coagulation have been studied during laboratory mental stress tasks 234,235 and during various naturalistic stressors. 236,237 In both situations, significant, but not always consistent, platelet abnormalities have been observed. Acute laboratory mental stress also causes hemoconcentration through stress-induced decreases in plasma volume, as observed in various studies.…”
Section: Coagulation Effectsmentioning
confidence: 91%
“…However, because blood samples were fortuitously obtained in 42 hypertensive patients before the large Hanshin-Awaji earthquake, investigators obtained repeat blood samples 7 to 14 days afterward to assess the effects of this acute stressor on coagulation parameters. 236 The earthquake induced transient increases in blood pressure; blood viscosity determinants, such as hematocrit and fibrinogen levels; and various hemostatic factors, including fibrin turnover and plasmin-␣ 2 -plasmin inhibitor complex, an activation marker of fibrinolysis. These parameters returned to normal levels by 4 to 6 months after the earthquake.…”
Section: Coagulation Effectsmentioning
confidence: 99%
“…These psychosocial factors are composed of depression, anxiety, personality and character traits as well as chronic and subacute life stress. 4,[10][11][12][13] A growing number of epidemiologic studies has suggested that anger and hostility are related to incidence of MI, 14 especially in older men. 14,15 Efforts to raise public awareness of these issues may carry a larger importance as terrorism remains a constant threat.…”
Section: Discussionmentioning
confidence: 99%
“…The attacks on the World Trade Center (WTC) on September 11,2001 were the most shocking and severe acts of terrorism ever experienced on American soil. The immediate psychological sequelae, including post-traumatic stress disorder (PTSD) and depression, following the terrorist attacks have been studied both nationwide 1 and locally 2 in Manhattan, New York City.…”
Section: Introductionmentioning
confidence: 99%
“…Pathophysiologic links appear to include increases in platelet aggregation or reactivity associated with anger expression 47 and hostility 48 ; between Type A/hostility and reduced bleeding time, as well as increased prostacyclin formation 49 ; and between enhanced platelet aggregation and mental stress related to increases in catecholamines and sympathetic nervous system activity. 50 …”
Section: Psychosocial Stress and Thrombosismentioning
confidence: 99%